Gifts of writing creative projects with words and art - Tchudi, Susan J. (Susan Jane) 1945-; Tchudi, Stephen 1942- (Scribner, 1980)
Gives suggestions for combining creative writing, calligraphy, and art work to produce unique and personal gifts such as stationery, postcards, posters, greetings cards, books of several types, and holiday projects.